Musyawarah Sebagai Upaya Penguatan Modal Sosial - Bayu Indra Laksana; Muhammad Haris; Saifunnajar Saifunnajar; Yefni Yefni (Jurnal at-Taghyir: Jurnal Dakwah dan Pengembangan Masyarakat Desa, 2025)
Digitalization can threaten social capital because technology reduces direct interaction and opportunities for deliberation, leading to increased individualism. This study aims to explore the role of deliberation in strengthening social capital in Karya Tani Village, Kempas District, Indragiri Hilir Regency. This research employs a descriptive qualitative approach, utilizing both primary and secondary data sources. Primary data is obtained through observations and structured in-depth interviews with informants, while secondary data is gathered from relevant literature and documents. The findings reveal that deliberation in Karya Tani Village functions not only as a decision-making tool but also as a mechanism for building social networks, trust, as well as shared norms and values within the community. This process creates an inclusive social climate where every voice is valued, reducing the potential for conflict and strengthening community relationships.Keywords: Deliberation, Social Capital, Strengthening